Proposed Corporate Strategy Formulation and Implementation Plan for PT Adhi Persada Properti - Kenny, Kenny; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
The commercial property construction sector which includes high-rise buildings and retail spaces, is growing fast with averages growth of demand at 13% for the following years. ADHI Persada Properti is a subsidiary of ADHI Karya, a construction company owned by the Government of Indonesia specialized in commercial property construction sector. Compared with their competitor, they gained very low performance with only 0.24% of the market share in 2011. Since the company just entered the market in 2009 while the parent company targeted the company revenue to grow at 30% for the following years, the company needs to revise its strategy in order to achieve growth.This research is conducted in order to propose new strategy for ADHI Persada Properti through the strategic management process. After conducting external and internal analysis by using the PEST Analysis, Porterâ€™s Five Forces analysis, Value Chain Analysis, and Parenting-Fit Matrix, it is identified that ADHI Persada Properti have several strength, weaknesses, opportunities, and threats.To propose new strategy for ADHI Persada Properti, the SWOT Analysis, the competitive advantage matrix, the BCG matrix, the GE Business Screen, and TOWS Matrix will be used.To Implement the proposed strategy, a series of program and action plan will be delveloped in each functional department of ADHI Persada Properti.Â